Infection prevalence of ovine fasciolosis in small-scale irrigation schemes along the Upper Awash River Basin - Asrat, M.; Petros, B.; Jobre, Y.; Peden, Donald G.; Shiferaw, Y.; Taddesse, G.; Mamo, M. (2005)
From November 2003 to October 2004, the prevalence rate of ovine fasciolosis in small-scale irrigation schemes found in three different agro-ecologic zones of the Upper Awash River Basin was assessed. An overall fasciolosis infection prevalence rate of 56.3% (729/1296) was recorded in examined sheep in the Upper Awash Valley. Statistical comparisons of results revealed that the infection prevalence in the highlands (62.9%) was significantly higher (p<0.05) than both mid-altitude (51%) and lowlands (52%). No statistically significant difference (p>0.05) was depicted between fasciolosis infection prevalence in mid-altitude and lowland study sites, as well as between age and sex categories of examined subjects. The overall wet season prevalence (59.2%) was significantly higher (p<0.05) than the dry season prevalence (53.6%). Similarly, prevalence in irrigated sites (60.8%) was significantly higher (p<0.05) than non-irrigated sites (50.4%). However, closer analyses of results showed that these differences between irrigated and non-irrigated sites were not statistically significant (p>0.05) in the highland sites and independent of any seasonal influence. On the other hand, irrigation has significantly increased (p<0.05) the prevalence of ovine fasciolosis in mid-altitude during the dry season and in lowlands during both the dry and wet seasons. These findings strongly suggest and warrant that special schemes are requires and should be instituted vis the risk level associated with agroecologic variations for the control of fasciolosis and other water-borne animal and human diseases in areas where agricultural development efforts involve irrigation systems.